Um estudo longitudinal sobre processos pedagógicos para a musicalização de um aluno com autismo e deficiência intelectual - Guizzo, Pedro Ivo Ximenes (Universidade Federal de São Carlos, 2024)
Teacher education in the most varied areas of knowledge permeates special education and didactics towards the students of Special Education in various ways. The purpose of this research was to investigate and raise data on pedagogical practices of a musical education teacher for a student with autism spectrum disorder (ASD) associated with intellectual disability (DI). This research focused on a case study of pedagogical practices in a certain teacher-student relationship in the context of music classes that occurred in the mid-2000s. The collection of information was done through semi-structured interviews through online platforms of video conference. The participant in question answered questions related to his teaching experiences with some students and more focused on their contact with the student Julius (autistic and intellectual disabilities, resulting from a Bourneville-Pringle syndrome staff) who attended private classes during fence ten years old. After data collection, analyzes and reflections on pedagogical procedures were made, as well as the importance of vocational training for specialized educational care and how the service was done in the cut of this study. Through the reports of the interviewed teacher and surveys made by family members, it is pointed out that several behaviors were encouraged over the ten years of monitoring musicalization to the student in question. Among the results, it is noteworthy that the hearing stimulation of certain sound frequencies provided a neurological maturity tangent to the reception of sounds. Other dynamics brought the student a series of learning, such as lighting and turning off the lights, as well as singing and dance through music, which were later very important tools for the student's appropriation over language and communication, considering that singing, for Student led him to access new words, and dancing gave him greater mastery over his body language. Finally, the effectiveness of a musical practice will be analyzed in students with severe disabilities, both in the pedagogical and development of the child, and regarding the quality of life of family members and the child.
A longitudinal study on pedagogical processes for the musicalization of a student with autism and intellectual disability
Keywords: Educação especial; Special education; Música; Music; Pessoa com deficiência; Disabled person; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO